2019
DOI: 10.3168/jds.2019-16515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of student transrectal palpation on early pregnancy loss in dairy cattle

Abstract: Transrectal palpation of the reproductive tract is the most common method for pregnancy determination in cattle and is considered a veterinary skill that new veterinary medicine (DVM) graduates should perform proficiently. However, using privately owned cattle to train students can be difficult because producers may believe that transrectal palpation by inexperienced students increases the risk of pregnancy wastage compared with examination by an experienced clinician. We used a randomized field trial of 1,216… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…RFM); the age of the animals was also recorded. Each water buffalo enrolled was submitted to a complete clinical examination with particular focus on the reproductive apparatus performed through visual examination of external genitalia, trans-rectal palpation and ultrasound according to the indication of Bond et al [38] (data not shown). Jugular blood was collected in tube containing serum separator (Vacutainer ® , Becton and Dickinson, Franklin Lakes, NJ, USA) at time of examination.…”
Section: Clinical Procedures and Serological Diagnosismentioning
confidence: 99%
“…RFM); the age of the animals was also recorded. Each water buffalo enrolled was submitted to a complete clinical examination with particular focus on the reproductive apparatus performed through visual examination of external genitalia, trans-rectal palpation and ultrasound according to the indication of Bond et al [38] (data not shown). Jugular blood was collected in tube containing serum separator (Vacutainer ® , Becton and Dickinson, Franklin Lakes, NJ, USA) at time of examination.…”
Section: Clinical Procedures and Serological Diagnosismentioning
confidence: 99%
“…There is controversy among authors about how rectal palpation affects pregnant cows. Some studies suggest that rectal palpation in early stages may be a major cause of pregnancy loss [ 20 , 21 ], while others provide evidence that palpation does not affect fetal loss [ 10 , 22 ] although it may be a stressor [ 8 ]. This fact, combined with the limited resources of veterinary schools, the increase in the number of students in lecture halls and the low availability of animals for teaching due to welfare regulations, reduces teaching opportunities in live animals [ 23 ], justifying the increased use of simulators in theriogenology.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors claim that teaching rectal palpation is a practice that induces a stress response in cows, as well as a reduction in vagal tone [ 8 ] and that repetitive rectal palpation and insemination practices can affect bovine health and productivity [ 9 ]. Other studies suggest the safety of using live animals for bovine palpation training [ 10 ]. The use of simulators in high education enables practical training by repetition in similar to real-life situations, ensuring the correct performance of the technique before applying it to live animals [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have been criticized for faulty methodology, including lack of control groups. 16,35 More recent studies have demonstrated that PPR does not contribute to a higher pregnancy loss compared to doing nothing or doing TRUS. 16,24,34,35 Pregnancy loss with TRUS was reported between 4.2% and 6.5% when sonography was performed at 25 to 30 days post breeding and then rectally palpated 60 days later.…”
Section: Accuracy Of Pregnancy Ppr and Trus Monitoring Techniquesmentioning
confidence: 99%